Sustainability Development Goals Initiatives of Multinational firms: Empirical Evidence from Emerging Economy - Iftikhar Ahmed; Abubakr Saeed (NUML International Journal of Business & Management, 2023)
MNCs are regarded as one of the essential actors within the private sector that have a greater capability and outreach to address these wicked global challenges identified by the UN in 2015. Surprisingly, despite their important role in achieving SDGs, there is a lack of knowledge on the nature and extent of MNCs’ engagement in sustainable development programs (van der Waal and Thijssens, 2020). This study aims to address this issue by examining the characteristics (organizational size, and location) that influence firms’ engagement in SDGs initiatives that target to increase positive externalities. The results suggest that size and location exert a positive impact on the firm’s involvement in activities that increase positive externalities. These results have important theoretical and policy implications.